2021
DOI: 10.3390/ijerph18179094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tweets Containing Information Related to Rheumatological Diseases on Twitter

Abstract: Background: Tweets often indicate the interests of Twitter users. Data from Twitter could be used to better understand the interest in and perceptions of a variety of diseases and medical conditions, including rheumatological diseases which have increased in prevalence over the past several decades. The aim of this study was to perform a content analysis of tweets referring to rheumatological diseases. Methods: The content of each tweet was rated as medical (including a reference to diagnosis, treatment, or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
(69 reference statements)
0
11
0
1
Order By: Relevance
“…This is congruent with previous research that showed that user interest in Twitter was significantly focused on certain areas of the study. In a study about rheumatological illnesses, user interest was focused on only two of the areas of the ones included in the research, and in another paper about side effects associated with glucocorticoids, interest was focused on two adverse effects [55,56].…”
Section: Major Findingsmentioning
confidence: 99%
“…This is congruent with previous research that showed that user interest in Twitter was significantly focused on certain areas of the study. In a study about rheumatological illnesses, user interest was focused on only two of the areas of the ones included in the research, and in another paper about side effects associated with glucocorticoids, interest was focused on two adverse effects [55,56].…”
Section: Major Findingsmentioning
confidence: 99%
“…In everyday practice, rheumatologists are confronted with misinformation on general health topics, as described above, and also with specific fake news in the spectrum of rheumatic and musculoskeletal diseases. A Spanish study [57] analysed the content of a random sample of original tweets on Twitter, mainly about rheumatoid arthritis and osteoarthritis, 1,093 classified as medical and 421 as non-medical. A small rate of false information was found (4.4%), a little higher for therapeutics (5.8%).…”
Section: Fake News In Rheumatologymentioning
confidence: 99%
“…Patients' knowledge about their disease and better patient-physician communication can improve patient's treatment adherence and eventually the clinical outcome [22,23]. Social media and mobile communication applications can be important instruments for effective education and communications for patients as well as physicians [24,25]. Combining social media platforms and digital health technologies may have added benefit on communication between patients and health providers, monitoring disease activity, disease management and education [26].…”
Section: Discussionmentioning
confidence: 99%